Comparing MOOC Adoption Strategies in Europe: Results from the HOME Project Survey - Jansen, Darco; Schuwer, Robert; Teixeira, Antonio; Aydin, Cengiz Hakan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
Much of the literature and the academic discussion about the impact of Massive Open Online Courses (MOOC) in institutional strategic planning has been centred on the US context. However, data shows that although the US are responsible for the largest MOOC platforms and the most successful course provision, it is the European region which accounts for the highest percentage of global MOOC participation. Differently from the US Higher Education system framework, however, in Europe public policy and in particular the European Commission is now driving MOOC institutional uptake. Given the very different institutional, political and cultural contexts, it is interesting to analyse how in these two different regions Higher Education institutions are responding to the challenges of the MOOC phenomena and are integrating it in their own strategic planning.The current research presents the first attempt to conduct a benchmarking study of institutional MOOC strategies in Europe and the US. It's based on a survey launched by the EU-funded project HOME and compares results with a similar survey launched in the US. Results show that are significant differences in how US and European institutions understand the impact of massive forms of open education and also how they perceive the efficiency of digital education and online learning.